The impact of mindfulness on nurses’ perceived professional benefits: the mediating roles of workplace spirituality and work-life balance - Lin, Yapeng; Jiang, Changchun; Pan, Yujing; Xu, Ziqing (Frontiers in Psychology, 2024)
This study delves into the effects of mindfulness on workplace spirituality, work-life balance, and perceived professional benefits among nurses operating in the high-pressure environments of hospitals in Jiangxi Province, China. Utilizing a robust sample of 303 valid questionnaires and employing partial least squares (PLS) analysis, the research uncovers a significant positive relationship between mindfulness and workplace spirituality. Furthermore, it demonstrates how both workplace spirituality and work-life balance serve as crucial mediators in enhancing nurses’ perception of their professional benefits. The findings illuminate the potential of mindfulness training in substantially elevating job satisfaction and reducing burnout among nurses. The study not only reinforces the value of mindfulness in the healthcare sector but also advocates for its integration into professional development programs and healthcare policies. By doing so, it aims to bolster the overall wellbeing and professional effectiveness of nurses facing the myriad challenges inherent in demanding healthcare environments. This study contributes to the growing discourse on mindfulness in occupational settings, highlighting its pivotal role in enhancing both the personal wellbeing and professional capabilities of healthcare professionals.